Anxiety Description of Social Workers in Assisting Children in Conflict with the Law - M. Hikmal Yazid (Journal of Computer Science Advancements, 2023)
Anxiety, a pervasive emotion in the realm of social work, takes center stage in the experiences of professionals dedicated to assisting children entangled in the legal system. This study undertakes a comprehensive exploration of the nuanced landscape of anxiety among social workers, delving into the background, aims, scope, methodology, and key findings. Against the backdrop of escalating rates of youth involvement in criminal activities, the study aims to unravel the psychological dimensions of social workers tasked with the rehabilitation and support of juvenile offenders. Utilizing a mixed-methods approach, the research investigates the correlation between case severity, institutional support, coping mechanisms, and the anxiety levels experienced by social workers. The findings not only reveal varying degrees of anxiety but also underscore the significant influence of organizational support and coping strategies. This study contributes valuable insights for practitioners, policymakers, and educators, emphasizing the need for tailored interventions to support the well-being of social workers engaged in this emotionally demanding field. As social work continues to intersect with the legal complexities surrounding juvenile justice, a nuanced understanding of anxiety becomes imperative for fostering effective and sustainable interventions.